Effectiveness of a Mixed Martial Arts-Based Training Program in Reducing Obesity and Improving Cardiovascular Health Among Women in Indonesia - Surya Adi Saputra; Septiani Dewi Hamni; Exie Shirley; Helen Knowles (Inspiree)
The  purpose  of  the study. To develop and validate a comprehensive Body Fighter Camp Model and Training Program specifically designed for women in Indonesia, addressing the growing obesity epidemic and its associated health risks. The study aims to create an effective mixed martial arts-based exercise intervention that can simultaneously improve body composition and cardiovascular health.